2021
DOI: 10.1111/phn.12946
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in homecare setting: An Italian validation study

Abstract: Objective: Medication errors are a concern in overall the world. Although there are studies that investigate what may be the main causes that lead to the genesis of the medication error in the home care setting, there is no tool that correlates knowledge, attitudes, and behavior to medication errors in the context of home care. This study aimed to psychometrically test to the questionnaire on knowledge, attitudes, and behaviors in the administration of medication in the new setting: home care setting.Design: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Home health care has been defined as “the health care of patients living at home with the support of health care professionals (primarily nurses) employed by a professional home care organization” (Meyer‐Massetti, 2018a). Home health care is becoming increasingly popular due to a steadily ageing population and an increase in chronic diseases (Ayele et al., 2017) but knowledge of medication errors still seems exclusively associated with the hospital setting (Almanasreh et al., 2016; Ayele et al., 2017; Cain et al., 2012; Dionisi et al., 2021b; Giannetta et al., 2020a; WHO, 2016). The importance of analyzing this phenomenon in the home care setting lies in the difference of this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Home health care has been defined as “the health care of patients living at home with the support of health care professionals (primarily nurses) employed by a professional home care organization” (Meyer‐Massetti, 2018a). Home health care is becoming increasingly popular due to a steadily ageing population and an increase in chronic diseases (Ayele et al., 2017) but knowledge of medication errors still seems exclusively associated with the hospital setting (Almanasreh et al., 2016; Ayele et al., 2017; Cain et al., 2012; Dionisi et al., 2021b; Giannetta et al., 2020a; WHO, 2016). The importance of analyzing this phenomenon in the home care setting lies in the difference of this setting.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite this increasing importance, 9 current levels of research intensity are inconsistent with the contributions of home care services to the entire health care sector. 8,10,11 Previous research has explored patient safety issues, 12,13 the problems experienced by patients with chronic diseases and their caregivers 14 as well as the working conditions and health of home healthcare workers. 15,16 In addition to these topics, the question of how to measure and improve patient satisfaction with health care services is considered particularly essential.…”
Section: Highlightsmentioning
confidence: 99%
“…Despite the many risks of safe home care, there are no accurate statistics on the subsequent adverse complications [ 17 , 18 ]. A review of the literature showed that most studies dealt with hospital safe care [ 19 , 20 ] and little attention has been paid to safe home care [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%